Identification of Ulnar Artery Perforators Using Color Doppler Ultrasonography - Ishiko, Megumi; Yano, Koichi; Onode, Ema; Takamatsu, Kiyohito (Journal of Reconstructive Microsurgery, 2020)
Background The ulnar artery perforator (UAP) flap, which is hairless, thin, and pliable, has been used for the reconstruction of soft tissues from the finger to the elbow. Preoperative planning is essential for a perforator flap surgery, and there are some tests to identify perforators. Color Doppler ultrasonography (US) with a high-frequency transducer helps in detecting decreased flow in smaller vessels, such as perforators. The purpose of this study was to determine the anatomical locations and origins of perforators arising from the ulnar artery using color Doppler US in healthy volunteers.Methods Forty forearms of 20 healthy volunteers were included in the study. Perforators arising from the ulnar artery, within 100 mm proximal to the pisiform, were investigated using color Doppler US with a high-frequency transducer.Results A total of 205 perforators were identified. On comparing the locations in each 20 mm section from the pisiform, the largest number of perforators was 58 (28%), within 20 mm proximal to the pisiform. The axial view demonstrated 44 (21%), 64 (31%), 32 (16%), and 65 (32%) perforators in the radial, ulnar, superficial, and deep aspects of the ulnar artery, respectively. Fifty-two and 28 essential perforators were supplied by the UAPs arising from the superficial and ulnar aspect within 20 mm proximal to the pisiform and between 21 and 40 mm proximal to the pisiform, respectively, while elevating the UAP flap.Conclusion This is the first study to assess the UAP using color Doppler US. Identification of UAP using color Doppler US can be used as a preoperative assessment for reliable elevation of a UAP flap.
Keywords: perforator flap; ulnar artery perforator; color Doppler ultrasonography